Waste candle soot derived carbon nanoparticles: A competent alternative for the management of Helicoverpaarmigera. (February 2021) - Pandey, Rashmi; Siddiqui, Shafia; Saurabh, Sharad; Pankaj, Aditya; Singh, Pradhyumna Kumar; Parmar, Devendra; Singh, Shiv; Mishra, Manisha
Abstract: Helicoverpa armigera (Lepidoptera: Noctuidae) is considered as one of the foremost pests of global agriculture. This pest is contemplated for substantial economic loss apart from the socio-economic and environmental costs associated with its control. Farmers adopt several strategies for the control of this pest but the cost associated with these strategies is always a big question. This is the first time when waste-candle soot (CS) derived carbon nanoparticles (CNPs) are explored for the putative toxicity to H. armigera . In the present study, the entomotoxic effects of CNPs on H. armigera were investigated and compared with that of commercially available multi-walled carbon nanotubes (MWCNTs). Larvae fed on both the nanomaterials exhibited significant weight reduction and enhanced levels of antioxidant enzymes. Moths developed from the treated larvae exhibit very poor egg-laying capacity and poor egg hatchability. However, these entomotoxic effects were found more noticeable in larvae and moths fed on CNPs that eventually led to the complete cessation of the population build-up of H. armigera . These findings advocate the candidature of CNPs as a cost-effective alternative for efficient control of H. armigera in pest management programs. Graphical abstract: Image 1 Highlights: The entomotoxic effect of CS derived CNPs on Helicoverpa armigera is investigated. CNPs caused significant weight reduction and increased oxidative stress in larvae. CNPs completely stop the population buildup of H. armigera . CNPs may be used as a competent alternative for H. armigera pest management.